Assessing historical thinking and understanding : innovative designs for new standards - VanSledright, Bruce A., ....- (S.l. : Routledge, 2014)
Assessing Historical Thinking and Understanding advocates for a fundamental change in how educators think about making sense of learners' developing cognition and understanding in history. Author Bruce VanSledright argues that traditional and typical standardized testing approaches are seldom up to the task of measuring the more complex understandings students are asked to attain, as they cannot fully assess what the student knows. Rather, he points forward along a path toward changes in learning, teaching, and assessing that closely aligns with the Common Core State Standards. He delves into the types of history knowledge the standards require, illustrates how they can be applied in-use in history learning contexts, and theorizes how the standards might fit together cognitively to produce deep historical understandings among students in teaching-learning contexts. By providing a variety of assessment strategies and items that align with the standards, and identifying rich, useful assessment rubrics applicable to the different types of assessments, he offers an important resource for social studies teachers and curriculum writers alike.
Keywords: Geschiedenis ; onderwijs